Playing on reality: do geomodels improve the perception of geographical terms?. Issue 2 (3rd April 2018) - Czigány, Szabolcs; Császár, Zsuzsa; Kiss, Kinga; Halmai, Ákos; Lóczy, Dénes; Nagyváradi, László; Pirkhoffer, Ervin
ABSTRACT: Remodeling of geography education has been an ongoing challenge recently. Constructivist pedagogy, employing tools of problem and model-based learning, offers new opportunities to meet these challenges. Geomodels, flumes and stream tables may ease the understanding of geographic processes through hand-on-experience for students. With a computer-controlled geomodel, we analyzed the development of 36 high school students' terminology in the fields of potamology and remote sensing. Potamology terms, provided after the experimental session, were more focused and reflected the information perception and fixation during the experiment. Three weeks later the terminology of the students indicated a partial fixation of the relevant terms. When students' terminology on remote sensing was analyzed, the pre-experiment terms were loosely connected to the topic. Over the class, students' terminology increased in the field of potamology. Although it became more topic-specific and focused, students' remote sensing terminology still contained a large number of off-topic terms by the end of the experiment and three weeks later. Our findings revealed one of the major weaknesses of the Hungarian educational system, i.e. teachers are forced to follow the conventional geographical curricula, therefore hindering their adaptation to cutting-edge educational methods and the learning-by-doing approach of the Western European and North American syllabi.